CORRELATION OF RAPID DIAGNOSTIC DIPSTICK TESTS WITH BACTERIOLOGICAL CULTURE AND ANTIBIOTIC SUSCEPTIBILITY IN PEDIATRIC URINARY TRACT INFECTIONS - Farha; Dr Ramanath K (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Timely diagnosis of pediatric urinary tract infections (UTIs) is crucial to prevent renal scarring and chronic complications. Conventional urine culture is the gold standard, but its long turnaround time delays antibiotic therapy. Rapid dipstick tests detecting leukocyte esterase (LE) and nitrite offer faster screening. Aim: To correlate the performance of dipstick LE and nitrite tests with urine culture and to determine the antimicrobial susceptibility profile of uropathogens isolated from pediatric UTI cases. Methods: A prospective study was conducted in 100 children (2–12 years) suspected of UTI at Index Medical College Hospital, Indore .Clean-catch urine was analyzed by dipstick, microscopy, and quantitative culture. Isolates were identified by biochemical methods, and antimicrobial susceptibility testing (AST) was performed using the Kirby-Bauer method per CLSI (2023). Statistical correlation between dipstick and culture was analyzed. Results: Culture positivity was 38%. E. coli (47.4%) was the leading isolate, followed by Klebsiella pneumoniae (18%), Pseudomonas aeruginosa (10%), Proteus mirabilis (8%), and Enterococcus faecalis (6%). Sensitivity and specificity for LE and nitrite were 90.1% and 78.7%, 92.5% and 92.5%, respectively. Combined LE + nitrite yielded 95.5% diagnostic accuracy (p < 0.001). E. coli isolates showed >80% sensitivity to nitrofurantoin and amikacin but >65% resistance to β-lactams. Conclusion: Rapid dipstick screening correlates strongly with culture results and can guide empirical therapy until confirmatory culture and AST are available. Routine implementation can enhance early management and antibiotic stewardship in pediatric UTIs.